2022
DOI: 10.1155/2022/2906189
|View full text |Cite
|
Sign up to set email alerts
|

Severe Quantitative Scale of Acanthosis Nigricans in Neck is Associated with Abdominal Obesity, HOMA‐IR, and Hyperlipidemia in Obese Children from Mexico City: A Cross‐Sectional Study

Abstract: Background. Acanthosis nigricans (AN) is a clinical sign that commonly occurs in obesity; however, its specificity and sensitivity have been controversial. It is unknown if AN severity degree can be a useful marker for cardiometabolic disorders screening. We suggest that the stratified analysis of AN severity degree in neck by Burke’s scale could be a useful tool in the screening of cardiometabolic alterations in obese children. Objective. The aim of this study was the association of AN severity degree in neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Cardiometabolic risk factors associated with obesity may include acanthosis nigricans, insulin resistance (IR), elevated blood pressure, and dyslipidemia, which may later lead to CVD and T2DM. A recent study by Garcia et al ( 10 ) found that children affected by obesity with grade 3 acanthosis nigricans (the degree of severity in the neck by Burke's scale) were associated with increased waist circumference (WC), triglycerides (TGs), low-density lipoprotein cholesterol (LDL-C), total cholesterol, and homeostatic model assessment for IR (HOMA-IR), which might lead to vascular alterations. Similarly, our group also previously found that the majority of children with acanthosis nigricans (43%) were in the upper tertiles of the ratio of triglycerides to high-density lipoprotein cholesterol (TG: HDL-C) ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiometabolic risk factors associated with obesity may include acanthosis nigricans, insulin resistance (IR), elevated blood pressure, and dyslipidemia, which may later lead to CVD and T2DM. A recent study by Garcia et al ( 10 ) found that children affected by obesity with grade 3 acanthosis nigricans (the degree of severity in the neck by Burke's scale) were associated with increased waist circumference (WC), triglycerides (TGs), low-density lipoprotein cholesterol (LDL-C), total cholesterol, and homeostatic model assessment for IR (HOMA-IR), which might lead to vascular alterations. Similarly, our group also previously found that the majority of children with acanthosis nigricans (43%) were in the upper tertiles of the ratio of triglycerides to high-density lipoprotein cholesterol (TG: HDL-C) ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children in Northern India with obesity and AN had greater HOMA-IR scores and lower adiponectin concentrations compared to children with obesity but without AN [25]. Additionally, Burguete-García et al reported similar results, where Mexican children with a Burke Score of 3 had significantly greater HOMA-IR values than children with lower Burke scores [61]. Nithun et al also reported that AN and the Burke Scores were also associated with HOMA-IR values in patients 2-24 years of age [27].…”
Section: Discussionmentioning
confidence: 94%
“…A previous analysis of NHANES data indicated that adult men and women who self-identified with diabetes had 2.1 and 3.9 times greater risk, respectively, for underreporting energy intake [ 50 , 60 ]. Evidence that AN is associated with insulin resistance comes from several studies [ 25 , 27 , 61 , 62 ]. Children in Northern India with obesity and AN had greater HOMA-IR scores and lower adiponectin concentrations compared to children with obesity but without AN [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study on 95 obese school-aged patients showed that severity of neck AN, according to Burke’s scale, correlated with diastolic blood pressure ( p = 0.001) and blood levels of triglycerides ( p = 0.02), and inversely correlated with adiponectin ( p = 0.02) [ 60 ]. The majority of data show that subgroups of subjects with AN have the most severe IR profiles, as expected.…”
Section: An and Irmentioning
confidence: 99%